Weed management in irrigated castor (Ricinus communis L.) through herbicides: WEED MANAGEMENT IN CASTOR - ISHWAR SINGH,; M S RATHORE,; M L MEHRIYA,; R S CHAWRA,; M S CHANDAWAT, (Journal of Oilseeds Research, 2013)
A field experiment was conducted to find out most suitable and cost effective weed management practice for irrigated castor grown on the light textured soils of Western Rajasthan. Ten treatment combinations comprising of four herbicides with or without inter culture along with weedy, weed free check and farmers practice were compared in Randomized Block Design with three replications. Three season's pooled results revealed that pre-emergence application of pendimethalin @ 1.0 kg/ha + inter culture 40 days aftersowing (DAS) produced maximum seed yield of 3652 kg/ha with weed control efficiency of 96.4% besides maximum net return of ` 74,464/ha and B:C ratio of 3.78. The weed competition index was also observed to be lowest in thistreatment (0.4%). However, pendimethalin @ 1.0 kg/ha (pre-emergence) + inter culture 40 DAS, fluchloralin @ 1.0 kg/ha (pre-plant incorporation) + inter culture 40 DAS and weed free plots remained at par with each other. Application of either quizalofop-ethyl or fenoxaprop-p-ethyl @ 50 g/ha at 25 DAS also brought down the weed stand and weed drymatter significantly compared to weedy check though the extent of control was not equivalent to weed free plots. This treatment (preemergence application of pendimethalin @ 1.0 kg/ha + inter culture 40 DAS) validated at five sitesin farmer'sfields recorded higher seed yield and net return compared to farmer's practice of weed control.